Karakterisasi Yoghurt Fungsional dengan Penambahan Karaginan dan Spirulina sp. - Fitriah Khairul (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2026)
Yoghurt is a fermented dairy product produced by lactic acid bacteria, such as Lactobacillus bulgaricus and Streptococcus thermophilus, and has potential as a functional food. Carrageenan functions as a stabilizer to improve texture, while Spirulina sp. serves as a source of bioactive compounds that may enhance antioxidant activity. This study aimed to evaluate the functional characteristics and sensory quality of yogurt fortified with carrageenan and Spirulina sp., and to compare it with commercial yoghurt. The parameters analyzed included viscosity, antioxidant activity (DPPH method), total phenolic content, and organoleptic properties. The results showed that the fortified yogurt had lower viscosity (280 cP) compared to commercial yogurt (1836.7 cP), which may be attributed to differences in the type of stabilizers used. However, the fortified yoghurt exhibited higher antioxidant activity (68.5 ppm) than commercial yogurt (106.8 ppm), indicating stronger antioxidant capacity, along with higher total phenolic content (1.8 mg GAE/g compared to 1.4 mg GAE/g). Despite these advantages, commercial yogurt received higher preference scores across all sensory attributes. The fortified yogurt was characterized by a greenish-white color, neutral aroma, and thinner texture. Overall, carrageenan and Spirulina sp.-fortified yogurt shows potential as a functional food; however, further optimization of sensory characteristics is required to improve consumer acceptance. Keywords: Antioxidant, L. bulgaricus, organoleptic, total phenolic, viscosity